2015
DOI: 10.1002/anie.201506711
|View full text |Cite
|
Sign up to set email alerts
|

Clickable Nucleic Acids: Sequence‐Controlled Periodic Copolymer/Oligomer Synthesis by Orthogonal Thiol‐X Reactions

Abstract: Synthetic polymer approaches generally lack the ability to control the primary sequence, with sequence control referred to as the holy grail. Two click chemistry reactions were now combined to form nucleobase-containing sequence-controlled polymers in simple polymerization reactions. Two distinct approaches are used to form these click nucleic acid (CNA) polymers. These approaches employ thiol-ene and thiol-Michael reactions to form homopolymers of a single nucleobase (e.g., poly(A)n ) or homopolymers of speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 48 publications
(11 reference statements)
1
59
0
Order By: Relevance
“…At the same concentration of AuNSs and AuNPs, the AuNSs overall exhibited much greater absorbance than the AuNPs (Fig. 35 After DNA conjugation to the Au nanocrystals and centrifugation or filtration, UV-Vis measurements of the corresponding eluents or supernatants, showed that ∼76 and ∼60 DNA strands were conjugated to the AuNPs and AuNSs respectively. 39 Next, nucleic acid interactions were utilized to couple the AuNPs and AuNSs with the silica coated UCNPs.…”
Section: Resultsmentioning
confidence: 97%
“…At the same concentration of AuNSs and AuNPs, the AuNSs overall exhibited much greater absorbance than the AuNPs (Fig. 35 After DNA conjugation to the Au nanocrystals and centrifugation or filtration, UV-Vis measurements of the corresponding eluents or supernatants, showed that ∼76 and ∼60 DNA strands were conjugated to the AuNPs and AuNSs respectively. 39 Next, nucleic acid interactions were utilized to couple the AuNPs and AuNSs with the silica coated UCNPs.…”
Section: Resultsmentioning
confidence: 97%
“…While in recent years, Mirkin and co‐workers have pioneered the use of spherical nucleic acids for gene uptake and cells and regulation, many of these studies have primarily focused on building nucleic acid micellar or liposomal structures . To expand the materials set for co‐encapsulating nucleic acids and hydrophobic drugs within a single carrier, we report here the design and implementation of synthetic DNA analogs—namely click nucleic acids (CNAs)—for synthesizing PLGA‐based polymer nanoparticles that sequester high loadings of DNA.…”
mentioning
confidence: 99%
“…Recently, valuable advances have been made in the field of sequence‐controlled polymerization. Iterative multi‐step approaches provide excellent sequence‐fidelity but are tedious to conduct and therefore limited to oligomers and smaller polymeric chains . Template‐based strategies, polymerizations based on multicomponent reactions, and the polymerization of sequence‐controlled precursors allow for higher molecular weights but are limited to relatively simple repetitive patterns.…”
Section: Methodsmentioning
confidence: 99%
“…The resulting poly(HFIPA‐ alt ‐OVE) was orthogonally postfunctionalized via radical thiol–ene click reaction and subsequent amidation . It is well known that the properties of polymers can be altered significantly by chemical postfunctionalization and numerous recent reports deal with the modification of polymers by thiol click chemistry, Cu‐catalyzed alkyne–azide click reaction (CuAAC), amidation reactions, and many others, including combinations thereof. Our conceptual approach introduced allowed for preparation of a small library of alternating copolymers using a single type of parent copolymer and diversifying subsequent orthogonal postmodification.…”
Section: Methodsmentioning
confidence: 99%